Answer: x=-5
Step-by-step explanation:
Answer:
Step-by-step explanation:
You don't specify what you're supposed to do, so I'll make an educated guess.
Given the sequence f(1) = 4, f(n) = f(n − 1) + 11, find the first 5 terms:
f(1) = 4
f(2) = f(2 - 1) + 11 = f(1) + 11 = 4 + 11 = 15
f(3) = f(2) + 11 = 15 + 11 = 26
f(4) = f(3) + 11 = 26 + 11 = 37
f(5) = 37 + 11 = 48
3x - 5 = -26
<u>step 1:</u>
subtract +5 on each side because you have to do the inverse operation
<u>step 2:</u>
3x= -21
<u>step 3:</u>
now divide 3 on each side
the answer is -7
<u />
Hope this helped!
<u />
<em>TheOneAndOnlyLara~</em>